2016
DOI: 10.1111/ans.13609
|View full text |Cite
|
Sign up to set email alerts
|

Pain in pancreatic cancer: review of medical and surgical remedies

Abstract: Pancreatic cancer is a malignant tumour with very poor prognosis and a chance for 5-year survival is approximately 6%. One of the main symptoms of this neoplasm is pain, mostly of neuropathic origin, which significantly decreases the quality of life and impairs the functional activity of patients. The most common treatment of pain in pancreatic cancer is conservative therapy which is based on analgesic ladder rules established by the World Health Organization. Unfortunately, it is not always effective and it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 61 publications
0
23
0
6
Order By: Relevance
“…Sympathectomy and related procedures (splanchni-cectomy, celiac plexus block) appear to have a potential role in reducing visceral pain, primarily from pancreatic cancer. 4,10,25,28,71 A recent Cochrane analysis of the use of cervicothoracic or lumbar sympathectomy for neuropathic pain and complex regional pain syndrome (CRPS) concluded that the existing data are insufficient to support a recommendation with regard to sympathectomy for these pain conditions. 104 There is essentially no modern neurosurgical literature on this topic, and procedures that appear to be effective are generally performed either by anesthesiologists (celiac plexus block), or either thoracic or general surgeons (splanchnicectomy, sympathectomy).…”
Section: Sympathectomymentioning
confidence: 99%
“…Sympathectomy and related procedures (splanchni-cectomy, celiac plexus block) appear to have a potential role in reducing visceral pain, primarily from pancreatic cancer. 4,10,25,28,71 A recent Cochrane analysis of the use of cervicothoracic or lumbar sympathectomy for neuropathic pain and complex regional pain syndrome (CRPS) concluded that the existing data are insufficient to support a recommendation with regard to sympathectomy for these pain conditions. 104 There is essentially no modern neurosurgical literature on this topic, and procedures that appear to be effective are generally performed either by anesthesiologists (celiac plexus block), or either thoracic or general surgeons (splanchnicectomy, sympathectomy).…”
Section: Sympathectomymentioning
confidence: 99%
“…[13][14][15] The resulting pain has both nociceptive and neuropathic components which complicates management, especially as most patients are not surgical candidates at presentation. 16 Direct intervention at the level of the celiac plexus acts downstream of the pain generators to disrupt the transmission of the pain signal regardless of signal type, and is therefore effective in simultaneously treating both types of pain.…”
mentioning
confidence: 99%
“…Фентанил ТТС, n=22 [2]. Несмотря на наличие гендерных различий у пациентов IIА и IV стадий отсутствовали статистически достоверные различия по уровню интенсивности болевого синдрома, что может объясняться влиянием также других факторов, что требует дальнейшего изучения [3]. Снижение интенсивности боли в группах наблюдения в динамике сопряжено с высокобальными значениями по шкале ESAS в группе приема трамадола, что может объясняться наличием НЯ, влияющих на качество жизни [7].…”
Section: нежелательные явления морфина сульфат N=13unclassified
“…Учитывая высокую заболеваемость и смертность, позднюю диагностику и преобладание агрессивных гистологических вариантов с низкой резектабельностью и отсутствием должной эффективности современных видов терапии, пациенты с раком поджелудоч-ной железы (РПЖ) также нуждаются в проведении паллиативной терапии на определенной стадии онкологического континуума [2]. Купирование болевого синдрома, как правило, является основной составляющей паллиативной терапии [3]. Изучение клинико -эпидемиологических особенностей ХБС на региональном уровне у пациентов с РПЖ является основой формирования персонализированной дорожной карты анальгетической терапии в условиях морфо -функциональных изменений желудочно -кишечного тракта на фоне ЗНО.…”
Section: Introductionunclassified